2018
DOI: 10.1038/s41366-018-0077-2
|View full text |Cite|
|
Sign up to set email alerts
|

In utero exposure to gestational diabetes and adiposity: does breastfeeding make a difference?

Abstract: In utero GDM exposure was associated with greater adiposity during childhood and adolescence. Breastfeeding in early infancy from mothers with GDM was not associated with greater adiposity in children and thus should still be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In this environment-wide and epigenome-wide association study, we systematically examined associations of over four hundred exposures with adiposity in a unique Chinese birth cohort, as well as the association of DNA methylation with adiposity. Building on the previous studies in this birth cohort (19)(20)(21)23), we not only confirmed established risk factors, such as maternal second-hand smoking (48), but also added by identifying novel exposures not reported in previous EWAS in western settings (8,9), such as consumption of ASB and soymilk. The comparison with RCTs or MR studies support a role of higher birth weight, dairy intake, binge eating and possibly earlier puberty in adiposity.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In this environment-wide and epigenome-wide association study, we systematically examined associations of over four hundred exposures with adiposity in a unique Chinese birth cohort, as well as the association of DNA methylation with adiposity. Building on the previous studies in this birth cohort (19)(20)(21)23), we not only confirmed established risk factors, such as maternal second-hand smoking (48), but also added by identifying novel exposures not reported in previous EWAS in western settings (8,9), such as consumption of ASB and soymilk. The comparison with RCTs or MR studies support a role of higher birth weight, dairy intake, binge eating and possibly earlier puberty in adiposity.…”
Section: Discussionsupporting
confidence: 66%
“…For example, in the "Children of 1997" birth cohort, a large cohort in Hong Kong, the associations of sugar-sweetened beverages (19), breastfeeding (20), milk consumption frequency (21), sleep duration (22) and parental smoking (23) with childhood and adolescent adiposity have been examined, with some important differences detected. The associations for breastfeeding in Hong Kong are much more similar to those seen in randomized controlled trials (RCTs) than those typically seen in western settings (20). To take advantage of this unique setting, we conducted an environment-wide and epigenome-wide association study, to identify further potential drivers of adiposity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were eligible for inclusion (Hui et al, 2018; Martens et al, 2016). The details for both studies are included in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…BMI: One study reported on BMI z-score. Hui et al, in a prospective birth cohort, reported that breastfeeding does not attenuate the association between GDM exposure in utero and BMI in the offspring at 3 months of age (Table 1; Hui et al, 2018).…”
Section: Resultsmentioning
confidence: 99%